Feasibility Test of Diabetes Mellitus Educational Video Learning Media - Ahmad Ahmad; Indra Rahmad; Muhtar Muhtar; Zulkarnain Zulkarnain; Fadlurrahmi Fadlurrahmi (Green Publisher Indonesia, 2025)
This study aims to determine the feasibility of audio-visual media used as educational media for diabetes mellitus. The type of research used is Research and Development (R&D). The product developed is Animation-Based Audio Visual. This development research is modified from the 4-D learning device development model consisting of 4 stages, namely define, design, develop, and disseminate. Validity test data is obtained from the validation sheet based on the assessment of expert validators. There are two types of validation sheets used, namely media validation sheets and material validation sheets. The results of the study and data analysis show that the video is very feasible to use when reviewed based on media feasibility with a validity of 85.00% and a reliability of 88.57%. Based on these results, it can be concluded that the video is very feasible to use in the learning process.